DESIGNING EFL STUDENTS’ WORK SHEET BASED ON ISLAMIC VALUES AND CULTURE-RELATED CONTENT - Neti Lastri; Mila Arizah (Universitas Putera Batam, 2020)
The objectives of this research are to: 1) discover the learning needs and students’ needs of the eighth grade students of SMP Islam Terpadu Fathona Baturaja toward the learning source for reading text, 2) design the appropriate materials of English Reading textfor the eighth grade students of SMP Islam Terpadu Fathona Baturaja. To collect the data, the researcher used four instruments (documents, needs analysis questionnaire, expert judgment evaluation rubric, and satisfaction questionnaire). The methodology of this research was research and development (RnD). The participants were 16. They were given needs analysis questionnaire. The results of needs analysis were as the guideline to develop syllabi for the worksheet’s chapters. The first draft materials of product were evaluated by the experts. The results of expert judgment, for all aspects, had a mean score 1 which could be categorized as proper. There was only 1 aspect that was 0.82 which was proper too. The researcher then established the product to be evaluated by the English teachers. The results could be categorized as Very Good. The final product in the form of EFL Worksheet with the implementation of Islamic values and related culture for the eighth grade students of SMP Islam Terpadu Fathona Baturaja